Anisotropic Scattering Characteristics of a Radially Multilayered Gyrotropic Sphere - Lei Cao; Yongpin Chen; Kai Kang (International Journal of Antennas and Propagation)
We present a new closed-form solution to the scattering of a monochromatic plane wave by a radially multilayered gyrotropic sphere using the T-matrix method. This approach can be utilized to investigate the interactions of a plane wave and a gyrotropic spherical scatterer of multiple layers with each layer characterized by both permittivity and permeability tensors. Based on the completeness and noncoplanar properties of vector spherical wave functions (VSWFs), analytical expressions of the electromagnetic fields in each gyrotropic layer are first derived. The boundary conditions are then applied on each discontinuous interface to obtain the scattering coefficients. Validations are made by first comparing the radar cross section (RCS) values of a 2-layered gyrotropic sphere with that computed from the full-wave finite element method (FEM) simulation and then reducing the general case to uniaxial case to compare the RCS values with the published results computed by Fourier transform combined with VSWFs method; in both cases good agreements are observed. Several specific cases are fully explored to investigate how the RCS are influenced by the parameters of the multilayered spherical structure. The results show that when both electric and magnetic gyrotropy tensors are considered, the RCS of the multilayered spherical scatterer can be suppressed or enhanced, depending on proper configurations of the material parameters.